(untitled) (Research, Society and Development, 2020)
Milker’s nodule is a dermatovirosis caused by the Poxviridae virus family, affecting humans and animals. In human beings, it is presented progressively from maculopapular lesions with erythematous base going by target shape, exudative, regenerative papilomatous nodule with a crust. The study aimed to describe a Case Report that will contribute to health multiprofessional knowledge in dermato-infectious specialties with look like presentations, in order to extend the differentials diagnosis. It has been an observational, descriptive, retrospective study in Case Report format of a inpatient admitted at the Tropical Diseases Hospital of the Federal University of Tocantins (HDT-UFT), in the city of Araguaína-TO. Data were collected by electronic medical records consultation and health professional’s reports who were involved in the patient care following Research Ethic Committee approval and Informed Consent Form signing to allow the paper and images publication with no hazard to the patient. The patient has presented classical lesions in the palmar region, as well as on scalp and knee, although histopathological tests were not performed due the hospital service limitations. It is important to the clinicians to understand the cutaneous forms of this viral disease, to perform the best treatment and to advice preventive measures to the secondary infection. There must be a deeper study about this subject in order to implement preventive actions by supervisory bodies responsible for bovine and caprine animals to animal-related infection in humans.